Winter virus season impact on acute dyspnoea in the emergency department. (10th September 2019) - Christiaens, Hanae; Charpentier, Sandrine; Houze‐Cerfon, Charles‐Henri; Balen, Frederic
Abstract: Objective: To compare the epidemiology of dyspnoea presented to emergency departments (EDs) during and of winter virus season (WVS). Methods: This is a monocentric retrospective cohort study. All patients attending to the ED of the Rangueil University Hospital (Toulouse, France) for dyspnoea in September 2016 (off WVS period) and January 2017 (during WVS period) were included. The primary endpoint was the final diagnosis. The patients' medical profiles, care duration, seriousness and futures were studied as secondary endpoints. Results: A total of 395 patients were studied: 125 patients during off‐peak influenza season and 270 patients during the peak influenza season. The incidence of patients attending because of dyspnoea increased significantly during WVS (4.2% of ED presentations during the off WVS period versus 8.4% during the WVS period, P  < 0.001). Patients attending the ED because of dyspnoea during WVS period were significantly older with more extensive medical backgrounds and more serious diseases. Most of those patients were hospitalized (54%), and largely in the geriatrics department. Conclusion: The incidence of patients attending because of dyspnoea doubled during the WVS period, with patients who were older and had more complex histories. This time‐consuming population largely requires hospitalization and may be one of the causes of the emergency department's overcrowding during epidemics.